Effectiveness of Media-Assisted Inquiry Learning Models Interactive Flip Book to Improve Critical Thinking Undergraduate Students - Anggraeni, Desak Made; Saphira, Hanandita Veda (Studies in Learning and Teaching, 2025)
This study investigates the effectiveness of an inquiry-based learning model supported by interactive flipbook media in enhancing students' critical thinking skills (CTS) on the topic of optics. The research employed an experimental design with a repeated measures pre-test and post-test format, without a control group. The sample consisted of 40 fourth-semester students enrolled in the Optical Waves course during the 2024/2025 academic year. CTS was assessed using a standardized test instrument. Data were analyzed using paired t-tests or Wilcoxon tests, N-Gain analysis, effect size calculations, and independent t-tests. The findings indicate that the media-assisted inquiry learning model significantly improves students' CTS, as evidenced by: (1) a statistically significant increase in CTS scores; (2) N-Gain values falling within the medium to high range; (3) an effect size of 1.4, categorized as strong; and (4) consistent average N-Gain scores across classes at the 5% significance level. The study concludes that the use of interactive flipbook media within an inquiry-based framework is effective in fostering students' CTS.